2023
DOI: 10.1021/acsearthspacechem.2c00299
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Study on Vanadium Isotope Fractionation among Species Relevant to Geochemistry

Abstract: The application of vanadium (V) stable isotopes to trace various geological and biological processes is an emerging field. Vanadium can exist in several redox states and in various coordination environments, such that its isotopic composition could be used to trace its exchange between different phases during these processes. In order to provide a basis for interpreting natural data, we have computed theoretical isotope fractionation factors of V among various species relevant to geological and biological envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
(241 reference statements)
0
2
0
Order By: Relevance
“…Coupled V–Fe isotope analysis has also shown that V in silicate minerals was released during chemical weathering and adsorbed on colloidal Fe (oxyhydr)­oxides, which were transported by water flow along the latosol profile . When V migrated between the aqueous and organic phases, the V isotope fractionation factor for the 51 V/ 50 V ratio varied between −0.1 and +1.35‰ …”
Section: Migration and Transformationmentioning
confidence: 99%
“…Coupled V–Fe isotope analysis has also shown that V in silicate minerals was released during chemical weathering and adsorbed on colloidal Fe (oxyhydr)­oxides, which were transported by water flow along the latosol profile . When V migrated between the aqueous and organic phases, the V isotope fractionation factor for the 51 V/ 50 V ratio varied between −0.1 and +1.35‰ …”
Section: Migration and Transformationmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21] Vanadium isotope compositions are generally reported as d 51 V values, which are the deviations of V isotope ratios relative to AA-V solution: 10 d 51 V = [( 51 V/ 50 V sample )/ ( 51 V/ 50 V AA ) − 1] × 1000&. Large V isotope fractionations have been predicted by theoretical and experimental studies, [22][23][24] and observed in natural samples, which implies their wide application to study geological processes. The distinct d 51 V in chondritic meteorite, 25,26 Martian, 27 lunar, 28 and terrestrial materials 29,30 were proposed to reect V isotope fractionation during planetary differentiation in the Solar System and the formation of the Moon.…”
Section: Introductionmentioning
confidence: 99%